Development and characterization of carbonaceous materials for supercapacitor electrode - Chen, Yutong (Nanyang Technological University, 2024)
In this project, the potential of Carbon Nanotubes (CNTs) to be electrodes of supercapacitors was explored. An interdigitated finger pattern was designed to optimize electrode structure and working efficiency. A low temperature CNT transfer method is applied to separate CNT synthesis from assembly, preserving device`s properties. During electrochemical properties testing, CNT samples were found shrunk after dropping electrolyte. Initial attempt to stabilize the CNTs is using silver conductive epoxy. Further study on the mechanism of shrinkage reveals that this phenomenon was caused by surface tension of electrolyte and capillary force during drying of silver epoxy. This phenomenon can also be called capillary densification. While initially capillary densification was considered problematic, it was found that capillary densification could improve sample`s electrochemical performance by increasing CNT density. Consequently, experiments were conducted to study the impact of different silver epoxy thicknesses on degree of capillary densification. Further research on exploration of surface modification techniques, mechanism of capillary densification and advance CNT fabrication methods are needed to achieve the target of utilized CNTs as electrodes of supercapacitor.